Global Economic Prospects, June 2012 : Managing Growth in a Volatile World - World Bank (Washington, DC, 2013)
The year began on a positive note. A marked improvement in market sentiment, combined with monetary policy easing in developing countries, was reflected in a rebound in economic activity in both developing and advanced countries. Industrial production, trade and capital goods sales all returned to positive territory, following the slow growth of the fourth quarter of 2011. Although debt levels in developing countries are lower, several countries (notably Jordan, India, and Pakistan) must reduce their structural fiscal balances to reduce debt to 40 percent of Gross domestic Product (GDP) by 2020 (or prevent debt-to-GDP ratios from rising further). As a result, sharp swings in investor sentiment and financial conditions will continue to complicate the conduct of macroeconomic policy in developing countries. In these conditions, policy in developing countries needs to be less reactive to short-term changes in external conditions, and more responsive to medium-term domestic considerations. A return to more neutral macroeconomic policies would also help developing countries reduce their vulnerabilities to external shocks, by rebuilding fiscal space, reducing short-term debt exposures and recreating the kinds of buffers that allowed them to react so resiliently to the 2008/09 crisis.